Biblical Hermeneutics In Contexts Of Armed Conflict. The Colombian Case - Casas Ramírez, Juan Alberto (2023)
The religious framework, Christian and mostly Catholic, with the growing emergence of Evangelical groups of Pentecostal and Neo-Pentecostal tradition, has played a fundamental role in the development of the armed conflict in Colombia. On the one hand, it came to promote biblically inspired discourses that legitimized or tolerated violence in order to defend and maintain traditionalist social and cultural structures; on the other, it has been a promoter or mediator of actions that seek peace, reconciliation and reparations for victims. In the latter sense, the processes of biblical reading carried out with affected and victimized communities in contexts of armed conflict have been a source for the collective construction of the historical memory of the facts, a way of healing and resignification of the trauma itself, an existential place of acceptance and openness to diversity and plurality, generators of strategies of reparation, non-repetition and personal and community rehabilitation.